The Effect of Interactive Digital Storytelling on Kindergarteners’ Learning of Challenging English Phonemes in their Foreign Language - Alhomaidhi, Shrowg (2025)
This thesis investigated the effectiveness of non interactive digital storytelling (DST) and different degrees of interactive digital storytelling (IDST) in addressing the challenges Saudi EFL kindergartners face in perceiving and distinguishing the English /p/ and /b/ phonemes. It also explored the kindergartners’ enjoyment of DST and different formats of IDST. The thesis involved 125 Saudi EFL kindergartners. The research design included four experimental groups—non-interactive DST, non-targeted IDST, targeted IDST, and highly-targeted IDST—and a control group with non-interactive DST. All experimental groups experienced the same story content presented in different formats, while the control group was exposed to a non interactive DST with different content. Data were collected using a pre- and post-test to measure children’s phoneme perception across words with varying familiarity based on their frequency in the kindergarteners’ curricula. Additionally, a five-point rating task was used to assess children’s enjoyment of different types of DST.